An Impact Evaluation of the Effects of Income Support Benefits on Aggregate Labour Supply - Javier Martín-Román; Ángel L. Martín-Román (Global Labor Organization (GLO), 2025)
This paper assesses the impact of the Agrarian Unemployment Benefit (AUB), a regionally targeted income support scheme introduced in Andalucía, Spain, in 1984. At its peak, the program covered more than 10% of the regional labour force, making it one of the most extensive welfare measures of its kind in Europe. Unlike most previous studies, which focus on micro-level effects of unemployment benefits, this research adopts a macroeconomic perspective to evaluate whether the AUB encouraged or discouraged labour force participation at the extensive margin. The analysis combines a theoretical model of labour supply decisions with the Synthetic Control Method (SCM), which provides a robust counterfactual based on regional data from 1980 to 1996. The results show that the AUB increased Andalucía's participation rate by about two percentage points in the years following its introduction. Nonetheless, the number of newly activated workers remained below the total number of beneficiaries, pointing to only partial compensation of disincentive effects. The study contributes by offering a macro-level evaluation of an income support program, developing a framework that clarifies incentive mechanisms, and applying SCM in this context for the first time. The findings yield relevant lessons for the design of modern welfare schemes and for current debates on place-based policies.
Keywords: J21; J65; H24; K31; C32; C54; 330; Labour supply; Labour force participation; Income support benefits; Synthetic Control Method